Impact of histology classification on pathologic treatment response and overall survival in distal esophageal cancer patients: a propensity matched analysis. Issue 8 (30th September 2020) - Saeed, Sabrina M; Naffouje, Samer; Mehta, Rutika; Hoffe, Sarah E; Fontaine, Jacques P; Lauwers, Gregory Y; Shah, Parth; Frakes, Jessica; Pimiento, Jose M
Abstract: Background: Esophageal squamous cell carcinoma (ESCC) has been linked to superior pathologic treatment response compared to esophageal adenocarcinoma (EAC) after neoadjuvant chemoradiation. However, the impact of histology on survival remains unclear. It has been suggested, based on epidemiologic similarities, that distal EAC should be grouped with gastric cancers as an entity distinct from distal ESCC, but there is little data to support this recommendation. We therefore aim to compare pathologic treatment response (PTR) and overall survival (OS) in patients with distal EAC versus distal ESCC. Methods: This retrospective cohort study included patients who underwent esophagectomy for distal esophageal malignancy. Histologic sub-groups were matched (1:1) using a propensity-score matching approach. Pre-operative clinical parameters, oncologic outcomes and survival were compared between groups. Results: 1031 distal EC patients, with a median age of 64.4 years and a male preponderance (86.5%), underwent esophagectomy at our institution between 1999 and 2019. 939 (91.1%) patients had a diagnosis of EAC and 92 (8.9%) had ESCC. A higher proportion of ESCC patients were female (26.1% vs. 12.1%; P < 0.01) and non-white (12.0% vs. 3.8%; P < 0.01). Propensity-score sub-analysis identified 75 matched pairs. Rates of pathologic complete response (58.0% vs. 48.9%; P = 0.67) and OS (43.0 vs. 52.0 months; P = 0.808) were not significantly different between matched groups. Conclusions: Although traditionally known to have a better overall PTR compared to EAC, ESCC patients in our large series did not show any improvement in PTR or OS. Treatment recommendations for patients with EAC and ESCC should consider tumor location in addition to histology.